A trend deduction model of fluctuating oil prices - Haiyan Xu; ZhongXiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2011)
Crude oil prices have been fluctuating over time and by a large range. It is the disorganization of oil price series that makes it difficult to deduce the changing trends of oil prices in the middle- and long-terms and predict their price levels in the short-term. Following a price-state classification and state transition analysis of changing oil prices from January 2004 to April 2010, this paper first verifies that the observed crude oil price series during the soaring period follow a Markov Chain. Next, the paper deduces the changing trends of oil prices by the limit probability of a Markov Chain. We then undertake a probability distribution analysis and find that the oil price series have a log-normality distribution. On this basis, we integrate the two models to deduce the changing trends of oil prices from the short-term to the middle- and long-terms, thus making our deduction academically sound. Our results match the actual changing trends of oil prices, and show the possibility of re-emerging soaring oil prices.
Keywords: Q41; Q47; C12; C49; F01; O13; 330; Oil Price; Log-normality Distribution; Limit Probability of a Markov Chain; Trend Deduction Model; OPEC